2017
DOI: 10.1021/acs.nanolett.7b01618
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Diffusion of Passive Tracers in Active Enzyme Solutions

Abstract: Colloidal suspensions containing microscopic swimmers have been the focus of recent studies aimed at understanding the principles of energy transfer in fluidic media at low Reynolds number conditions. Going down in scale, active enzymes have been shown to be force-generating, nonequilibrium systems, thus offering opportunity to examine energy transfer at the ultralow Reynolds number regime. By monitoring the change of diffusion of inert tracers dispersed in active enzyme solutions, we demonstrate that the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 34 publications
5
63
0
2
Order By: Relevance
“…These authors propose that the enhanced diffusion is due to conformational fluctuations that alter the enzyme's hydrodynamic radius. More surprisingly, a catalytically inert tracer has also been reported to diffuse faster in the presence of active enzymes (14), leading to the suggestion that the energy released during enzyme catalysis can be transferred to and harnessed by its environment. Directly contradicting the FCS results by Illien et al, Zhang et al and Günther et al recently reported no diffusion enhancement of aldolase using dynamic light scattering (15) and pulsed field gradient nuclear magnetic resonance (16), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These authors propose that the enhanced diffusion is due to conformational fluctuations that alter the enzyme's hydrodynamic radius. More surprisingly, a catalytically inert tracer has also been reported to diffuse faster in the presence of active enzymes (14), leading to the suggestion that the energy released during enzyme catalysis can be transferred to and harnessed by its environment. Directly contradicting the FCS results by Illien et al, Zhang et al and Günther et al recently reported no diffusion enhancement of aldolase using dynamic light scattering (15) and pulsed field gradient nuclear magnetic resonance (16), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…(22). The experimentally accessible substrate concentration is 10 −6 M < c S < 10 −3 M [12,14]. On the other hand, the value of the Michaelis constant K M differs between fast and slow enzymes.…”
Section: F Numerical Estimatesmentioning
confidence: 99%
“…In the presence of a gradient in substrate concentrations, enzymes exhibit collective motions in the direction of higher or lower concentrations [11,12]. Moreover, the enhanced diffusion of passive objects in enzymatic solutions have been observed independently [13,14]. * komura@tmu.ac.jp † andelman@tauex.tau.ac.il…”
Section: Introductionmentioning
confidence: 99%
“…[193] Thec hemotactic separation of biomolecules from am ixture has been demonstrated to be sensitive enough to sort molecules possessing identical physical properties that cannot otherwise be accomplished using currently known separation techniques By using fluorescence correlation spectroscopy (FCS) and dynamic light scattering (DLS) measurements it was further demonstrated that active enzymes molecules,m uch like microorganisms,w ere also able to influence significantly the dynamics of their surroundings (Figure 8a). [89] Thediffusivity of both micro-and nanoscopic tracers suspended in active enzyme solutions were enhanced as af unction of substrate catalysis in the system. This indicates there is reaction-induced force generation and controlled energy transfer at the molecular scale (Figure 8b,c).…”
Section: Nanoscale-and Ngstrçm-scale Systemsmentioning
confidence: 99%
“…[84][85][86][87][88] More surprisingly, enzymes were found to generate sufficient mechanical forces during catalysis and be capable of interacting significantly with their surroundings-much like living microorganisms and the artificial micromotors. [89] Going further down the scale,e xperiments with ngstrçm-sized catalysts also suggested correlated dynamics of active molecules and their surroundings during catalysis. [90] These observations not only opened up an ew research area on activity-induced force generation and attainment of precise control over the collective dynamics of colloidal assemblies,i ta lso led researchers to inquire if such behaviors were amanifestation of some universal interaction principles in systems driven away from equilibrium.…”
Section: Introductionmentioning
confidence: 99%